Biomarker Testing Patterns and Treatment Outcomes in Patients With Advanced Non-Small Cell Lung Cancer and MET Exon 14 Skipping Mutations: A Descriptive Analysis From the US - Asad Zadeh Vosta Kolaei, Fatemeh; Cai, Beilei; Kanakamedala, Hemanth; Kim, Julia; Doban, Vitalii; Zhang, Shiyu; Shi, Michael (Frontiers in Oncology, 2022)
Background: MET exon 14 skipping mutation (METex14) is observed in ~3% of non-small cell lung cancer (NSCLC) cases and has been shown to be an independent poor prognostic factor associated with shorter overall disease-specific survival. Broad molecular testing can identify this biomarker in patients with advanced NSCLC (aNSCLC) and allow patients to be matched with the appropriate targeted therapy. This study examines biomarker testing patterns and clinical outcomes of chemotherapy and immuno-oncology (IO) monotherapy in aNSCLC patients with METex14. Methods: A descriptive retrospective study was conducted using the Flatiron Health–Foundation Medicine Inc (FMI) clinico-genomic database. Patients with METex14 aNSCLC treated with systemic therapies were included in the biomarker testing analysis. The duration from specimen collection to reported results was assessed for PD-L1– and METex14-tested patients. Clinical outcomes were assessed in patients treated with chemotherapy or IO monotherapy. Real-world progression-free survival (rw-PFS) was estimated using Kaplan-Meier analysis. Results: Of 91 METex14 patients eligible for the biomarker testing analysis, 77% and 60% received PD-L1 and FMI next-generation sequencing (NGS) testing within 3 months post aNSCLC diagnosis. Of those assessed for both PD-L1 and METex14 (n=9), the median duration between specimen collection and reporting was 1 week shorter for PD-L1 than for FMI NGS. Median rw-PFS was 5.7 months (95% CI, 4.6-7.1) and 2.4 months (95% CI, 1.4-3.2) in patients receiving first-line chemotherapy (n=59) and IO monotherapy (n=18), with 3month rw-PFS rates of 78% and 33%. Median rw-PFS was 3.5 months (95% CI, 1.9-11.1) and 4.7 months (95% CI, 2.8-12.9) in patients receiving second-line chemotherapy (n=16) and IO monotherapy (n=23), with 3-month rw-PFS rates of 54% and 67%. Conclusions: The median time from biopsy to test results appears 1 week shorter for PD-L1 than for FMI NGS. Chemotherapy and IO monotherapy were the most common regimens utilized but with limited PFS.